Defining Place: Celebrating Context and Community - William Bruder (Oz, 1997)
The responsibility of the architect is very much about defining and celebrating the pragmatic and poetic needs of the client. A most important component of that charge, which is all too often ignored, overlooked, or insensitively misinterpreted, is searching for the defining markers of context and community from which a project's aesthetic presence will grow.